RNAi-mediated silencing of hepatic Alas1 effectively prevents and treats the induced acute attacks in acute intermittent porphyria mice - Yasuda, Makiko (National Academy of Sciences, 2014)
The acute hepatic porphyrias are inherited disorders of heme biosynthesis characterized by life-threatening acute neurovisceral attacks. Factors that induce the expression of hepatic 5-aminolevulinic acid synthase 1 (ALAS1) result in the accumulation of the neurotoxic porphyrin precursors 5-aminolevulinic acid (ALA) and porphobilinogen (PBG), which recent studies indicate are primarily responsible for the acute attacks. Current treatment of these attacks involves i.v. administration of hemin, but a faster-acting, more effective, and safer therapy is needed. Here, we describe preclinical studies of liver-directed small interfering RNAs (siRNAs) targeting Alas1 (Alas1-siRNAs) in a mouse model of acute intermittent porphyria, the most common acute hepatic porphyria. A single i.v. dose of Alas1-siRNA prevented the phenobarbital-induced biochemical acute attacks for approximately 2 wk. Injection of Alas1-siRNA during an induced acute attack significantly decreased plasma ALA and PBG levels within 8 h, more rapidly and effectively than a single hemin infusion. Alas1-siRNA was well tolerated and a therapeutic dose did not cause hepatic heme deficiency. These studies provide proof-of-concept for the clinical development of RNA interference therapy for the prevention and treatment of the acute attacks of the acute hepatic porphyrias.